Alkali-resistant basalt fiber sizing agent and preparation method of basalt fiber
By using a wetting agent composed of ZrOCl2 sol and coupling agent, an epoxy resin-ZrO2 film-basalt fiber structure is formed, and the problems of poor film formation and poor bonding effect of basalt fiber wetting agent in the prior art are solved, and the alkali resistance and mechanical properties of the fiber are significantly improved.
Patent Information
- Application Number
- CN202310614964.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-29
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-05-29
AI Technical Summary
The existing basalt fiber wetting agent has poor film formation effect, and the effect is poor after being combined with concrete, which affects the alkali resistance of the fiber.
Using a combination of ZrOCl2 sol, film forming agent, coupling agent, lubricant, antioxidant and pH adjusting agent, a ZrOCl2 sol and coupling agent hydrolysate are prepared, and an epoxy resin-ZrO2 film-basalt fiber structure is formed during the heating and curing process.
It significantly improves the alkali resistance and film formation effect of basalt fibers, improves the bonding with concrete, and enhances the mechanical properties and service life of the fibers.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sizing agents, and in particular to an alkali-resistant basalt fiber sizing agent and a method for preparing basalt fiber. Background Art
[0002] In the modern construction industry, building structures are tall, huge and diverse. In order to meet the development needs of building structures, a large amount of fibers are needed to reinforce cement-based composite materials. Cement is an alkaline substance, and the interior of cement-based materials is in an alkaline environment from beginning to end. Therefore, when using fibers for composite, the alkali resistance of the fibers needs to be guaranteed.
[0003] In the prior art, there are two main methods to improve the alkali resistance of fibers: first, changing the fiber formula; second, changing the sizing agent formula;
[0004] For example, the patent with publication number CN113321429A discloses an alkali-resistant basalt fiber sizing agent, specifically: by adding ZrO2 emulsion to the sizing agent, ZrO2 is enriched on the surface of the fiber, thereby protecting the fiber from corrosion by the alkaline environment and improving the alkali resistance; wherein, when the sizing agent is used, the alkali-resistant component needs to be evenly coated on the surface of the basalt fiber, and at the same time, it is necessary to further promote the adhesion of the sizing agent on the fiber surface with the help of the enrichment of zirconium oxide on the fiber surface, so as to ensure that the basalt fiber bundles do not fall apart and improve the overall alkali resistance;
[0005] However, ZrO2 emulsion has poor stability. It not only needs to be stirred constantly and dispersed with the help of ultrasound during preparation, but also, if the emulsion is not used in time, it will settle to the bottom during use, thus affecting the coating effect and clogging the pipeline. Furthermore, the use of zirconium oxide will occupy the fiber defect position, affecting the strengthening effect of the impregnation agent.
[0006] For another example, the patent with publication number CN103466963A discloses an alkali-resistant chopped glass fiber sizing agent, specifically: a certain proportion of polyacrylate film-forming agent, epoxy resin emulsion film-forming agent, and water-soluble epoxy resin film-forming agent are added to the sizing agent formula, and the alkali resistance of the fiber is enhanced by increasing the thickness of the surface sizing agent film;
[0007] However, a large amount of organic film-forming agent is used in the impregnating agent, which has poor bonding effect during mixing with concrete and is not convenient for large-scale mixing and use. Summary of the invention
[0008] In view of the technical problems that the current basalt fiber impregnating agent has poor film-forming effect and poor bonding effect after mixing with concrete, thereby affecting the alkali resistance of the fiber, the first object of the present invention is to provide an alkali-resistant basalt fiber impregnating agent; the second object of the present invention is to provide a method for preparing alkali-resistant basalt fiber;
[0009] In order to achieve the above object, the present invention adopts the following technical solutions:
[0010] The invention discloses an alkali-resistant basalt fiber impregnating agent, which comprises, by mass percentage, 6% to 10% of ZrOCl2 sol, 20% to 22% of a film-forming agent, 0.4% to 0.6% of a coupling agent, 0.1% to 0.3% of a lubricant, 1.0% to 3.0% of an antioxidant, 0.1% to 0.3% of a pH regulator and the remainder of deionized water.
[0011] A method for preparing basalt fiber by impregnation with the aforementioned sizing agent specifically comprises the following steps:
[0012] S1. Preparation of ZrOCl2 sol: Add ZrOCl2·8H2O powder to ethanol-water solution and mix well under stirring;
[0013] S2. Hydrolysis of coupling agent: fully dissolve the pH adjuster in deionized water, add the coupling agent while stirring, the stirring time is 20 to 40 minutes, and the rotation speed is 50 to 150 r / min.
[0014] S3. Preparation of the wetting agent: The film-forming agent, lubricant, ZrOCl2 sol, antioxidant and remaining deionized water are sequentially added to the mixed coupling agent hydrolyzate while stirring. After sufficient mixing, stirring is continued for 20 to 40 minutes at a stirring speed of 50 to 150 r / min to obtain the configured enhanced wetting agent.
[0015] S4. Preparation of alkali-resistant basalt fiber: The above-mentioned impregnating agent is evenly applied to the surface of the basalt fiber, and then the temperature is raised to 400-500°C and heated and cured for 8-15 hours to obtain a sample. The inventors have found that at this heating and curing temperature, epoxy resin-ZrO2 film-basalt fiber can be obtained. If the temperature is lower than 400°C, it is not conducive to the conversion of ZrOCl2 molecules into ZrO2.
[0016] <Beneficial effects achieved by this application>
[0017] First, it has better alkali resistance: compared with ordinary basalt fibers, the titanium ions on the surface of the basalt fibers in the present invention gather after film formation to form a protective layer; and at the same time, a dense ZrO2 coating is formed to hinder the mass transfer between the fiber surface and the alkaline solution, thereby improving the fiber's alkali resistance. Compared with the reinforcement method of adding ZrO2 suspension, the ZrO2 in the present invention is suspended in the system in the form of dissolved ZrOCl2 molecules before heating and curing. The present invention can avoid the phenomenon of pipeline blockage and poor coating effect caused by the sedimentation of ZrO2 particles during the production process.
[0018] Furthermore, the film-forming effect is better: the non-silane coupling agent is innovatively added in the present invention to change the interface energy between the basalt fiber and the cement, and to form a strong chemical bond between the interfaces, so that the film of the impregnating agent on the surface of the basalt fiber is denser and the film-forming effect is better.
[0019] Furthermore, the bonding property with concrete is better: compared with the method of using a large amount of organic impregnating agents to change the interface energy between basalt fiber and concrete, the present invention uses titanium ions to aggregate on the surface of the fiber membrane and then, when doped with concrete, can better bond with various inorganic substances in the concrete, further improving the strength, water resistance, aging resistance and service life of the reinforced concrete. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0021] The invention provides an alkali-resistant basalt fiber impregnating agent, the components of which include, by mass percentage, 6% to 10% of ZrOCl2 sol, 20% to 22% of a film-forming agent, 0.4% to 0.6% of a coupling agent, 0.1% to 0.3% of a lubricant, 1.0% to 3.0% of an antioxidant, 0.1% to 0.3% of a pH regulator and the remainder of deionized water.
[0022] Among them, ZrOCl2 sol mainly provides alkali-resistant ZrO2. Before heating and curing, ZrO2 is suspended in the system in the form of dissolved ZrOCl2 molecules, and during the dispersion process, the ZrOCl2 sol particles are in the range of several to several hundred nanometers, with a narrow distribution, and are easy to form a film on the fiber surface. No special chemical treatment process is required, and the heat curing treatment temperature is low, which can be applied to the normal production process of basalt fiber. The nanofilm of hundreds of nanometers will not cause other effects on the fiber body.
[0023] The preparation method of ZrOCl2 sol includes adding ZrOCl2·8H2O powder to ethanol-water solution and mixing them uniformly under stirring;
[0024] In the present application, the molar ratio of ethanol to water in the ethanol-water solution is 1:8, and the molar ratio of ZrOCl2·8H2O to the ethanol-water solution is 1:4 to 10. The ZrOCl2 sol prepared in the present application is added to a stable epoxy resin infiltrant emulsion, and the emulsion is formed into a sol-like state by adjusting the content of ethanol.
[0025] The film former is a key component of the sizing agent, with the largest usage amount, and has an important influence on the function and performance of the sizing agent. The film former in the present invention is specifically an epoxy resin emulsion (TH-811,) which has excellent bonding ability, can protect the basalt fiber from breakage and mechanical wear, and at the same time provide good bundling properties for the basalt fiber.
[0026] The two different reaction properties of the coupling agent itself combine the glass fiber with the resin and other high molecular polymers, play a bridging role, and achieve good interface bonding between inorganic and organic substances. The coupling agent in the present invention includes a silane coupling agent and a titanate non-silane coupling agent. Specifically, the silane coupling agent is at least one of A187, A151, and A171; the titanate non-silane coupling agent is at least one of n-butyl titanate and tetrapropyl titanate.
[0027] Among them, the titanate non-silane coupling agent in the coupling agent is the key to enhancing alkali resistance. During the production process, the non-silane coupling agent is hydrolyzed, and the active hydroxyl groups on the outside are combined with the hydroxyl groups on the surface of the basalt fiber in the form of hydrogen bonds. Under the action of high temperature in drying, the hydroxyl groups combined with hydrogen bonds undergo etherification reaction to remove water to form a strong covalent bond, thus achieving the coupling effect. Titanium ions are enriched on the surface of basalt fibers, which can improve the density of the film. Titanium ions can prevent alkaline solutions from reacting with basalt fibers, thus improving the alkali resistance of fibers.
[0028] The lubricant lubricates the surface of the basalt fiber and reduces wear. The lubricant in the present invention includes at least one of lithium nitrate, ammonium chloride, and polyethyleneimine polyamide salt;
[0029] Preferably, the lubricant comprises polyethyleneimine polyamide salt and ammonium chloride in a mass ratio of 1-2:10-20.
[0030] The antioxidant is mainly used to delay and inhibit the oxidation process of organic components in the infiltration solution, prevent aging and extend its service life. The antioxidant in the present invention is specifically didecyl oxalate.
[0031] The pH regulator can adjust the pH of the infiltration solution during preparation. The pH regulator in the present application is at least one of glacial acetic acid and citric acid.
[0032] The alkali-resistant basalt fiber impregnation liquid provided in the present application can enhance the wear resistance and corrosion resistance of basalt fibers, promote the bundling of fibers to reduce loose and broken fibers, prevent static electricity accumulation on the fiber surface, and improve the interaction between fibers and different matrices (including cement, polymers, etc.).
[0033] At the same time, the present invention provides a method for preparing basalt fiber by impregnating the aforementioned sizing agent, which specifically comprises the following steps:
[0034] S1. Preparation of ZrOCl2 sol: Add ZrOCl2·8H2O powder to ethanol-water solution and mix well under stirring;
[0035] S2. Hydrolysis of coupling agent: fully dissolve the pH adjuster in deionized water, add the coupling agent while stirring, the stirring time is 20 to 40 minutes, and the rotation speed is 50 to 150 r / min.
[0036] S3. Preparation of the wetting agent: The film-forming agent, lubricant, ZrOCl2 sol, antioxidant and remaining deionized water are sequentially added to the mixed coupling agent hydrolyzate while stirring. After sufficient mixing, stirring is continued for 20 to 40 minutes at a stirring speed of 50 to 150 r / min to obtain the configured enhanced wetting agent.
[0037] S4. Preparation of alkali-resistant basalt fiber: The above-mentioned impregnating agent is evenly applied to the surface of the basalt fiber, and then the temperature is raised to 400-500°C and heated and cured for 8-15 hours to obtain a sample. The inventors have found that at this heating and curing temperature, epoxy resin-ZrO2 film-basalt fiber can be obtained. If the temperature is lower than 400°C, it is not conducive to the conversion of ZrOCl2 molecules into ZrO2.
[0038] After the impregnating agent in the present invention is applied to the basalt fiber, it can effectively change the bundling and flexibility of the fiber, thereby improving its mechanical properties, and form a dense ZrO2 coating to hinder the mass transfer between the fiber surface and the alkaline solution, thereby improving the alkali resistance of the fiber.
[0039] Example 1
[0040] The present invention provides an alkali-resistant basalt fiber sizing agent, the components of which, by mass percentage, include:
[0041] 10% ZrOCl2 sol, 22% film-forming agent (epoxy resin emulsion), 0.6% coupling agent (A187: n-butyl titanate = 1:1), 0.3% lubricant (polyethyleneimine polyamide salt: lithium nitrate = 1:12.5), 3.0% antioxidant (didecyl oxalate), 0.1% pH adjuster (glacial acetic acid) and the balance deionized water.
[0042] Its preparation method comprises:
[0043] S1. Preparation of ZrOCl2 sol: Add ZrOCl2·8H2O powder to ethanol-water solution and mix well under stirring; the molar ratio of ethanol to water in the ethanol-water solution is 1:8, and the molar ratio of ZrOCl2·8H2O to the ethanol-water solution is 1:4.
[0044] S2. Hydrolysis of coupling agent: fully dissolve the pH adjuster in deionized water, add the coupling agent while stirring, the stirring time is 30 minutes, and the speed is 100r / min.
[0045] S3, preparation of the wetting agent: the film-forming agent, lubricant, ZrOCl2 sol, antioxidant and remaining deionized water are added to the mixed coupling agent hydrolyzate in sequence while stirring. After sufficient mixing, stirring is continued for 30 minutes at a stirring speed of 100 r / min to obtain the configured enhanced wetting agent.
[0046] S4. Preparation of alkali-resistant basalt fiber: The above-mentioned impregnating agent is evenly coated on the surface of the basalt fiber, and then the temperature is raised to 450° C. and heated and cured for 15 hours to obtain a sample.
[0047] Example 2
[0048] The difference between this embodiment and embodiment 1 is that: ZrOCl2 sol is 8%; the molar ratio of ZrOCl2·8H2O to the ethanol-water solution is 1:10; after the impregnation agent is applied to the surface of the basalt fiber, the temperature is raised to 500°C and heated for 8 hours to obtain multiple groups of parallel samples.
[0049] Example 3
[0050] The difference between this embodiment and embodiment 1 is that: the film-forming agent is 20%, the coupling agent is 0.5%; and the molar ratio of ZrOCl2·8H2O to the ethanol-water solution is 1:10.
[0051] Example 4
[0052] The difference between this embodiment and embodiment 1 is that: the film-forming agent is 20%, the pH regulator is 0.3%; and the molar ratio of ZrOCl2·8H2O to the ethanol-water solution is 1:10.
[0053] Comparative Example 1
[0054] The difference between this comparative example and Example 1 is that the ZrOCl2 sol is replaced by ZrO2 emulsion.
[0055] Comparative Example 2
[0056] The difference between this comparative example and Example 1 is that the coupling agent is replaced with at least one of KH550 (γ-aminopropyltriethoxysilane), KH560 (γ-glycidyloxypropyltrimethoxysilane), and KH570 (γ-methacryloxypropyltrimethoxysilane).
[0057] The test results of basalt fiber coated with the alkali-resistant impregnation solution of the present invention under optimized conditions include tensile breaking strength, single-filament tensile strength, single-filament tensile modulus, single-filament tensile strength after alkali resistance, and strength retention rate after alkali resistance.
[0058] Table 1
[0059]
[0060] As shown in Table 1, the sizing agent obtained under the optimal conditions in the embodiment, after being applied to the basalt fiber, can effectively change the fiber's bundling and flexibility, thereby improving its mechanical properties, and forming a dense ZrO2 coating to hinder the mass transfer between the fiber surface and the alkaline solution, thereby improving the fiber's alkali resistance. Compared with the comparative example, it has stronger mechanical properties and better strength retention after alkali resistance.
[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An alkali-resistant basalt fiber sizing agent, characterized in that : Its components, measured by mass percentage, include: 6% to 10% ZrOCl2 sol, 20% to 22% film-forming agent, 0.4% to 0.6% coupling agent, 0.1% to 0.3% lubricant, 1.0% to 3.0% antioxidant, 0.1% to 0.3% pH regulator and the balance of deionized water; wherein the ZrOCl2 sol is prepared by adding ZrOCl2·8H2O powder to a mixed solution of ethanol and water, the lubricant is composed of a mixture of a cationic lubricant and a polyethyleneimine polyamide salt, and the mass ratio of the cationic lubricant to the polyethyleneimine polyamide salt is 10 to 20:1 to 2.
2. The alkali-resistant basalt fiber sizing agent according to claim 1, characterized in that :The film-forming agent is epoxy resin emulsion.
3. The alkali-resistant basalt fiber sizing agent according to claim 1, characterized in that : The coupling agent includes a silane coupling agent and a titanate non-silane coupling agent.
4. The alkali-resistant basalt fiber sizing agent according to claim 3, characterized in that : The silane coupling agent is at least one of A187, A151, and A171; the titanate non-silane coupling agent is at least one of n-butyl titanate and tetrapropyl titanate.
5. The alkali-resistant basalt fiber sizing agent according to claim 1, characterized in that : The antioxidant is didecyl oxalate.
6. The alkali-resistant basalt fiber sizing agent according to claim 1, characterized in that : The pH adjusting agent is at least one of glacial acetic acid and citric acid.
7. A method for preparing alkali-resistant basalt fiber, characterized in that :Impregnating the basalt fiber into the alkali-resistant basalt fiber sizing agent as described in any one of claims 1 to 6.
Citation Information
Patent Citations
Alkali-resistant chopped glass fiber soakage agent
CN103466963A
Alkali-resistant basalt fiber impregnating compound and preparation method thereof
CN113321429A
Preparation of silica-zirconia viscous sol
JP1991083832A